Easing the Heavy Hand: Humanitarian Concern, Empathy, and Opinion on Immigration. Issue 3 (26th November 2013) - Newman, Benjamin J.; Hartman, Todd K.; Lown, Patrick L.; Feldman, Stanley
Abstract : The bulk of the public opinion research on immigration identifies the factors leading to opposition to immigration. In contrast, we focus on a previously unexplored factor yielding support for immigration: humanitarianism. Relying upon secondary analysis of national public opinion survey data and an original survey experiment, we demonstrate that humanitarian concern significantly decreases support for restrictive immigration policy. Results from our survey experiment demonstrate that in an information environment evoking both threat and countervailing humanitarian concern regarding immigration, the latter can and does override the former. Last, our results point to the importance of individual differences in empathy in moderating the effects of both threat and humanitarian inducements.